1991
DOI: 10.1002/jnr.490300109
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of GFAP synthesis by antisense RNA in astrocytes

Abstract: Glial fibrillary acidic protein (GFAP) accumulation is a prominent feature of astrocytic gliosis. The inhibition or delay in GFAP synthesis might delay scar formation resulting from an insult such as spinal cord injury or central nervous system (CNS) demyelination. The delay in the formation of a physical barrier might allow the neurons and oligodendrocytes to reestablish a functional environment. We delivered antisense GFAP RNA complexed with Lipofectin (LF), a cationic liposome, into cerebral astrocytes in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 39 publications
1
40
0
Order By: Relevance
“…The medium was changed 19 hr after antisense addition. Antisense GFAP mRNA was produced according to Yu et al (1991). A 1.25 kb HindIII restriction fragment was obtained from the 5Ј coding end of a 2.5 kb cDNA clone encoding GFAP (generous gift from Dr N. J. Cowan, New York University) and subcloned into PGEM 3z, a SP6/T7 riboprobe vector system (Promega, Madison, WI).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The medium was changed 19 hr after antisense addition. Antisense GFAP mRNA was produced according to Yu et al (1991). A 1.25 kb HindIII restriction fragment was obtained from the 5Ј coding end of a 2.5 kb cDNA clone encoding GFAP (generous gift from Dr N. J. Cowan, New York University) and subcloned into PGEM 3z, a SP6/T7 riboprobe vector system (Promega, Madison, WI).…”
Section: Methodsmentioning
confidence: 99%
“…Using antisense GFAP mRNA (Yu et al, 1991), we indeed have observed that phenotypic changes, consecutive to the decrease in GFAP synthesis, induced a functional shift to neurite-promoting elements.…”
mentioning
confidence: 90%
“…The involvement of GFAP in the formation of astrocytic processes was demonstrated by using antisense inhibition of GFAP expression (Weinstein et al, 1991), thus opening up the possibility of modulating astrogliosis induced by injury (Yu et al, 1991(Yu et al, , 1993Ghirnikar et al, 1994). We have shown previously that the blockage of astrocyte reaction after a spinal cord (SC) lesion via local pharmacological therapy permits some axonal regeneration .…”
Section: Abstract: Astrocytes; Cytoskeleton; Intermediate Filaments;mentioning
confidence: 99%
“…The demonstration of the major role of GFAP in the formation of astrocytic processes (Weinstein et al, 1991) opened up the possibility of modulating astrogliosis induced by injury in an in vitro model (Yu et al, 1991).…”
mentioning
confidence: 99%